2007
DOI: 10.1007/s00702-007-0790-9
|View full text |Cite
|
Sign up to set email alerts
|

Damage to oligodendrocytes in the striatum after MPTP neurotoxicity in mice

Abstract: We investigated the alteration of oligodendrocytes in comparison with that of astrocytes and microglia in the mouse striatum after MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropridine) treatment under the same conditions using Western blot analysis and Immunohistochemistry. In our Western blot analysis, four administrations of MPTP at 2-h intervals to mice produced the remarkable loss of TH (tyrosine hydroxylase) protein levels in the striatum after 3 and 7 days. In contrast, GFAP (glial fibrillary acidic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…After a 9 min rinse in 0.01 M PBS, the sections were incubated with biotinylated secondary antibody for 60 min and then with avidin-biotin peroxidase complex for 30 min at room temperature. Immunoreactivity was visualized using enzyme substrate kits (Vector Labs., Burlingame, CA, USA), as described previously Takagi et al 2007). Negative control study was performed using nonimmunostained IgG by omission of primary antibody, which showed no notable staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…After a 9 min rinse in 0.01 M PBS, the sections were incubated with biotinylated secondary antibody for 60 min and then with avidin-biotin peroxidase complex for 30 min at room temperature. Immunoreactivity was visualized using enzyme substrate kits (Vector Labs., Burlingame, CA, USA), as described previously Takagi et al 2007). Negative control study was performed using nonimmunostained IgG by omission of primary antibody, which showed no notable staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For CNPase immunostaining of the dentate gyrus, area of expression of CNPase-immunopositive profiles of dentate granule cell layer, molecular layer, and hilus in the stained sections was evaluated under a light microscope at a magnification of 4009 without the examiner knowing the experimental protocols. These areas were expressed as the area of the CNPase-immunopositive profiles per 1 mm 2 using the computer-associated image analyzer software, as described previously (Takagi et al 2007). All values were expressed as the means ± SE and statistical significance was evaluated by one-way analysis of variance (ANOVA) followed by Fisher's PLSD multiple comparison test (Stat View version 5.0, SAS Institute Inc., USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…MPTP selectively damages the dopaminergic nigrostriatal system, resulting in the loss of dopaminergic neurons in the substantia nigra and a reduction of dopamine in the striatum (Kurosaki et al 2004(Kurosaki et al , 2005Takagi et al 2007;Watanabe et al 2008). …”
Section: Introductionmentioning
confidence: 98%
“…Immunoreactivity was visualized using enzyme substrate kits (Vector Labs. ), as described previously Takagi et al 2007). Negative control study was performed using nonimmuned IgG by omission of primary antibody, which showed no notable staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%